Matrix representations of the coordinates of the atoms of the molecules of H2O and NH3 in operations of symmetry - M. Ivanova; L. Dospatliev (Trakia Journal of Sciences)
The molecule is a spatial arrangement of atoms that make it up. This arrangement defines its geometric structure. Knowing the geometry and ways to describe to great advantage in studying the electronic structure of molecules as between geometric and electronic structure there is a close connection.